Deteksi Kestabilan Genetik Ramet Kelapa Sawit Hasil Kultur In Vitro Menggunakan SSR - Cahyaningsih, Yuni Fitri; Wiendi, Ni Made Armini; Toruan-Mathius, dan Nurita (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTCommercial production of oil palm ramet requires the guarantee of high genetic stability. The objectives of this research were to determine 1) genetic diversity of ortet as source of explant, and 2) genetic stability of ramet derived from ortet propagated through tissue culture. Genetic stability analysis was done using ramet from five Tenera (D×P) oil palm ortets.As many as 20 ramets were randomly chosen from each ortet. A total of 100 ramets were used for genetic stability analysis. Genetic similarity analysis was analyzed using NTSyspc version 2.1 software with method Similarity for Qualitative Data and Unweighted Pair Group Method Aritmatic (UPGMA). The results indicated 20 SSR primer pairs were polymorphic and could form 44 alleles. As many as 80% of ramets from IS 3 ortet showed genetic similarity ranged from 97-100% to the ortet. All ramets derived from IS 10, IS 20 and IS 40 ortet had 90-100% of genetic similarity to its respective ortet. Futhermore, 95% of ramets from IS 39 ortet had 97-100% of genetic similarity to the ortet.Keywords: Elaeis guineensis Jacq., genetic similarity, tissue culture